2003
DOI: 10.1037/0022-3514.85.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention improves under stress: Implications for theories of social cognition.

Abstract: Three influential perspectives of social cognition entail conflicting predictions regarding the selectivity of performance under stress. According to the attention view, selectivity to the task-relevant attribute improves under stress because of reduced utilization of task-irrelevant attributes. According to the capacity-resource approach, stress depletes attentional resources wherefore selectivity fails for all but chronically accessible information. A third perspective, ironic process theory, similarly holds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
233
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(265 citation statements)
references
References 94 publications
(156 reference statements)
15
233
2
4
Order By: Relevance
“…Stress was induced by a procedure previously used by Chajut and Algom (2003). Before the actual task-shifting experiment, in which an explicit cuing procedure with two CSI levels was used, all subjects worked on a short intelligence test.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Stress was induced by a procedure previously used by Chajut and Algom (2003). Before the actual task-shifting experiment, in which an explicit cuing procedure with two CSI levels was used, all subjects worked on a short intelligence test.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
“…Following the procedure of Chajut and Algom (2003), subjects completed three multiple-choice tasks, each containing 10 items, at the beginning of the session. The first task was a wordselection task, in which subjects chose the word that did not fit semantically with the other words listed (e.g., table, chair, bird, scaffold, bed).…”
Section: Iq Scalementioning
confidence: 99%
See 1 more Smart Citation
“…However, enhanced levels of NA have been shown to influence memory for (Wessel & Merckelbach, 1997), or selective attention to (Chajut & Algom, 2003;Fenske & Eastwood, 2003;Finucane & Powers, 2010) peripheral stimuli, therefore suggesting that the spillover of attention to irrelevant stimuli might not be invariable, but instead flexibly modulated by situational factors (e.g., affective state). In line with this view, Schmitz and colleagues (Schmitz, De Rosa, & Anderson, 2009) showed that the size of the attentional focus could be modulated depending on the current affective state of the participant.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what occurs in high performing athletes, the medical literature has suggested that Bgood^stress can positively influence performance compared to Bbad^or no stress. 2,3 Thus, just as athletes spend extensive amounts of time training to overcome obstacles and stress, perhaps a part of medical education should involve ways to teach students and residents how to lessen negative stress and improve positive stress. Educating trainees about personal wellness is currently being addressed by the Accreditation Council on Graduate Medical Education (ACGME), which requires each residency program to provide resident and faculty education on trainee alertness and fatigue mitigation.…”
mentioning
confidence: 99%